PENGATURAN TINDAK PIDANA PENCABULAN SEJENIS BERDASARKAN HUKUM PIDANA INDONESIA - Prasetyo, Budi; Effendi, E; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In the Code of Criminal Indonesia have related settings of sexual crimes including sexual abuse offense. However, in the case of criminal acts of sexual abuse is often a kind of law enforcement officials to use a particular article in the Criminal Code criminalize same-sex obscene acts by adults against minors. The issue is important to note because it will affect the future of law enforcement. Existing provisions in the Criminal Code has not been specifically regulates the crime of sexual abuse of the kind, so very unfortunate to the perpetrators can not be in meshes with applicable law. The aim of this study is the first, knowing settings similar criminal acts of sexual abuse by the Indonesian Penal Both know whether the Indonesian criminal law rules have become effective to trap similar criminal sexual abuse.From these results it can be concluded that the First, arrangements similar criminal acts of sexual abuse by positive law which is regulated in Article 292 of the Criminal Code and Law No. 23 of 2002 on Child Protection. Settings on the kind of abuse in the new criminal law touching on aspects of child protection as victims and not criminalize a type of abuse committed by their fellow adults (homosexual), so that those can not be subject to legal sanctions if anyone feels aggrieved as a result of the acts of sexual abuse Second, the Criminal Code and the Child Protection Act and not running optimally effective because of the higher and increasing acts of sexual abuse against children today. Sanctions in the rules of criminal law concerning sexual abuse are often imposed on similar offenders who on average have not shown the spirit of consistent law enforcement. Suggestions of Author, First. It is expected that the legislators, especially the House of Representatives to create consistent rules of criminal law and capable of achieving justice for society and immediate improvements to the Indonesian criminal law rules terkhsusus rules relating to sexual crimes committed by those who are the same sex so that law and order can be created in accordance with the aspired according to the values of justice, benefits and actual certainty Both of the sanctions in the rules of criminal law concerning sexual abuse should be applied similar maximum penalty by law enforcement officials, especially judges in a verdict against the accused so as to provide a deterrent for the offender as well as preventive measures that certain criminals do not commit a crimeKeywords: A kind of abuse, Criminal Law Indonesia